Shear Punching of Amorphous Alloys under High-Frequency Vibrations - Hongzhen Li (Metals, 2019)
Although amorphous alloys possess many excellent properties, their practical application is limited due to the difficulty of plastic forming. In this work, an effective shear punching of amorphous alloys under high-frequency vibrations was proposed. Under the high-frequency vibration of the punch, the plastic powder was melted into a flexible punch due to the frictional heat generation effect and the viscoelastic heat effect and continued to flow downward under the extrusion of the ultrasonic head to plastically deform the amorphous alloy ribbon. The disordered structure of the amorphous alloys helps them get soft in a localized region during high-frequency vibrations, which can result in low-stress deformations that are different from amorphous alloys in the conventional state. We manufactured various shapes with area of 5 mm2 using high-frequency vibrations and a molten plastic viscous medium. The molds were shaped into the letters “B”, “M”, and “G” and the Chinese characters “工” and “大”. The shapes were made from Fe-based, Al-based, La-based, and Cu-based amorphous alloys. Our results show that shear punching of amorphous alloys under high-frequency vibrations is an effective and low-cost production method of amorphous alloy, which also provides a basis for the wide application of amorphous alloy.